VITELLOGENESIS IN LEPISMA SACCHARINA L., A CYTOCHEMICAL STUDY - SAREEN, M.L.; MITTAL, P.K.; SHARMA, RAJ (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1990)
The Ovary in L. Saccharina is of panoistic type. Each ovariole has been divided into six zones - Z1 to Z6. Z1 includes the terminal filament; Z2 comprises the germarium; Z3 comprises primary oocytes lying in pairs and each measuring about 45um x 600 am; in Z4 the oocyte measures from 60 umx60 um to 75um x 375 um and the oocytes lie in a single row; in Z5 the oocytes measure about 90 umx480 um and the follicular epithelium covering the oocytes secretes the chorion; Z6 is the pedicel. Cytochemical studies of the oocytes in the various zones and origin of yolk have been attempted.